PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER MODEL TUTORIAL INTERAKTIF UNTUK MATERI POKOK GARIS DAN SUDUT KELAS VII - Alfajri, Hadiyanta; Roza, Yenita; Saragih, Sehatta (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The aim of this research is to develop interactive computer-based tutorial for mathematics class VII topics of lines and angles. This research use development model by Borg and Gall modified by Sugiyono (2011). Development is done through the following steps: (1) potentials and problems; (2) data collection; (3) media design; (4) validation; (5) revision; (6) small group test; (7) revision; (8) large group test; and (9) revision. At the stage of potentials and problems, researchers created a needs analysis of the results of interviews with teachers of Mathematics. Based on the needs analysis, learning media developed for six class meetings. Learning media is validated by three experts and further revised based on the input from validators. The revised learning media was tested on a small group consist of five students of class VII. The learning media was revised and test in large group involved 21 students of class VII SMP N 1 Rengat. From the large group test results, the learning device improved. The result of data analysis and discussion shows that interactive computer-based tutorial for mathematics class VII topics of lines and angles are valid with an average value of 3.57 and is practical to use by students of class VII.